PENGEMBANGAN KEMAMPUAN PEMANFAATAN AI TOOLS UNTUK MENDUKUNG KESIAPAN KERJA MAHASISWA VOKASI DI ERA SOCIETY 5.0 - Damar Isti Pratiwi; Teguh Arifianto; Fathurrozi Winjaya; Rengganis Siwi Amumpuni (As-Sidanah, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed industrial skill demands, emphasizing human–machine collaboration rather than mere automation in the Industry 5.0 era. Vocational education institutions must therefore equip students with AI literacy and ethical digital competence to strengthen employability and workplace readiness. This community service program aimed to enhance vocational students’ ability to utilize AI tools for professional tasks and ethical technological engagement. Conducted through practice-based training, workplace simulations, and mentoring sessions for 96 students in Madiun City, Indonesia, the program integrated pre- and post-tests, performance assessments, and reflective evaluations. Results indicated significant improvement in students’ understanding of AI concepts, proficiency in using multiple AI tools (e.g., ChatGPT, Canva AI, Notion AI, QuillBot), and ability to create professional digital portfolios. Participants also demonstrated heightened awareness of digital ethics, data security, and responsible AI use. The program effectively improved employability skills, self-efficacy, and adaptability to technological changes. This initiative provides a sustainable model for embedding AI literacy into vocational curricula and preparing human resources capable of innovative collaboration with intelligent technologies in Industry 5.0..